Documental Hipias en la profundidad de la tierra - Coloma Maldonado, Karla Mishelle (2010)
This is a 35 minutes long documentary. Its main purpose is share information, mostly unpublished, about the Hipias, a Quito long gone civilization. Most of Quito inhabitants, and form Ecuador in general, believe that the pre-incaico civilization that lived in Quito was the Quitus-Cara, when in reality this was a name given to many different civilization and people that lived in that area. This documentary investigates and summarises all the recent discoveries found in and around la Florida which is located northwest of Quito. All of this new data shows there was a civilization named the Hipias who where the truly inhabitants of what we now know as Quito. Based on real data obtained thru many interviews with the archaeologists who discovered and investigated this civilization, this documentary shows the finding of the necropolis of the Hipias. This is a deposit that helped understand how did this long gone culture viewed the world around them, its way of thinking, its society, its everyday life, all of this has been possible by the study, analysis and understanding of the found objects, it symbols and all of the components. The main purpose of this project is to show and inform the currents inhabitants of Quito, how were their ancestors, their beliefs and mainly, the diversity that has been inherited.